Produtividade do algod\~ao no Brasil: Uma análise da mudança estrutural - Isabela Romanha de Alcantara; Roberta Vedana; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The cultivation of arboreal cotton, which represented almost a quarter of the national production and occupied half of the area harvested in the 1970s, was practically extinct, while the production of herbaceous cotton grew and consolidated since the 2000s. This study evaluated the productivity of herbaceous cotton from 1974 to 2019, a period in which the country minimized external dependence and became a reference in the international market, accounting for 15.6% of world exports. An attempt was made to verify a possible structural break in productivity. The weevil plague, the optimization of natural resources and technological improvement, as well as the creation of producer organizations and associations, stimulated the productive restructuring, in which the production units were relocated in the territory. The results indicated that productivity changed in intercept and trend in 1999. The annual growth rate was 2.03% before and 2.43% afterward. The level change was 81.91%. Institutional and productive transformations were responsible for productivity gains, which allowed for productive expansion and contributed to a land-saving effect of 12.2 million hectares over time.
Keywords: Q1; O4; R1; 330; cotton crop; productive restructuring; structural rupture; productivity